Animal Futurity: An Introduction to the Special Issue. Issue 1 (2nd January 2022) - Castle, Nora; Champion, Giulia
ABSTRACT: In order to contextualise the Animal Futurity special issue, this introduction will examine some of the ways in which humans have historically (and continuing to the present day) been enmeshed with the lives of non-human animals (NHAs), setting the stage for why alternative imaginaries for human-NHA relations are urgently necessary. This contextualisation highlights the tension between human reliance on (and relationships with) NHAs and their increasing invisibilisation. It puts pressure on the ways in which NHAs are compromised by their implication in global capital markets, and opens up avenues for the discussions of ethical consideration and care that are carried through into the articles themselves. The introduction will then conclude by offering a roadmap of the articles in the issue.